The Optimal Conditions of Xylanase Production Using Empty Fruit Bunch Raw Biomass by Marine Isolate LBF-001 - Hans Wijaya; Ahmad Thontowi; Nanik Rahmani; Yopi Yopi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Several xylanases have already been studied. However, only a few xylanases derived from marine microorganisms has been reported. Marine bacterium LBF-001 was isolated from Pari Island Kepulauan Seribu, Indonesia. The purpose of this study is to identify isolate LBF-001 using 16S rDNA gene and to optimise the medium conditions for the xylanase production i.e. concentration of biomass, nitrogen source, pH and temperature. Based on 16S rDNA gene analyses, LBF-001 isolate has 99% similarity with Bacillus pumilus HNS70 (KF933667). Fermentation process to produce xylanases was conducted using several agricultural residues under solid-state fermentation (SSF). The optimum condition for xylanase production by B. pumilus LBF-001 was using a medium containing  2.5% empty fruit bunch and 0.6% lactose broth, at pH 6.5, temperature 30 oC, under submerged fermentation with shaking at 150 rpm for 48 h fermentation. The optimised condition resulted higher xylanase activity, i.e. 10.85 U/mL.